2010
DOI: 10.1007/s12291-010-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the vitamin D receptor and the androgen receptor gene associated with the risk of urolithiasis

Abstract: Transcriptional activity of the vitamin D receptor (VDR) gene is regulated by androgen receptor (AR normocalciuric (mean=21.62 ± 3.384 vs. 20.11 ± 3.182; P=0.034

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The SNP's in the VDR gene is also known to be associated with several diseases such as neurological diseases, different types of cancer, and diabetes in different populations [10][11][12][13][14]. Role of VDR polymorphisms in diabetes may be justified by making the argument that due to allelic differences in the VDR gene; the VDR mediated signaling of Vitamin D may get affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP's in the VDR gene is also known to be associated with several diseases such as neurological diseases, different types of cancer, and diabetes in different populations [10][11][12][13][14]. Role of VDR polymorphisms in diabetes may be justified by making the argument that due to allelic differences in the VDR gene; the VDR mediated signaling of Vitamin D may get affected.…”
Section: Discussionmentioning
confidence: 99%
“…VDR is encoded by the VDR gene located on the chromosome 12 (12q12-q14). Several VDR polymorphisms have been reported in case of different populations suffering from different metabolic diseases [10][11][12][13]. In the recent years, these polymorphisms are also known to be associated with both the risk of occurrence of diabetes in the various diabetic populations [14].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of genetic epidemiological studies have been conducted to explore the relationship between SNPs and calcium urolithiasis and the results are inconclusive [19][20][21][22][23][24][25][26][27][28]. As one of the most important genes related with calcium metabolism, VDR gene has earned special concern.…”
Section: Commentmentioning
confidence: 99%
“…Nishijima et al [25] observed that the Taq I t allele was associated with a 5.2-fold increase in the risk for severe stone disease and increased urinary calcium levels in adult Japanese patients. Mittal et al [23] indicated that the Taq I Tt polymorphism and the Fok I Ff polymorphism are significantly associated with calcium stones in Indian people. However, there are also contrasting results have been reported.…”
Section: Commentmentioning
confidence: 99%
“…Mossetti et al [8] found associations between the BsmI and TaqI polymorphisms and idiopathic hypocitraturia in recurrent calcium oxalate stone disease. The most recent study by Mittal et al [9] indicated that both Tt genotype of TaqI polymorphism and Ff of FokI polymorphism demonstrated a significantly higher risk for stone formation (OR = 1.830 and 3.559, respectively). However, the analysis by Chen et al [10] revealed that the BsmI polymorphism of the VDR gene was not a suitable genetic marker for urinary stone disease.…”
Section: Introductionmentioning
confidence: 99%